Socrates view on sophrosyne - Predanocyová, Ľubica (Sincronía, 2025)
Sophrosyne is one of the fundamental values, which were reflected in the Greek classical philosophy. The paper is concentrated to provide image of that virtue in philosophical legacy of Socrates. The author points to the search content, structure and location sophrosyne in the context of other Greek areté, and points to the possible intentions sophrosyne in the practical socio-political life, such how it Socrates theory constitutes.